Mesh dependence analysis for simulating unsteady cavitation around a plane convex hydrofoil. Issue 1 (1st September 2022) - Puga, D; Escaler, X; Hidalgo, V; Luo, X
Abstract: The mesh significantly influences the quality of the numerical results in computational fluid dynamics (CFD) problems due to its correlation with turbulence models. In the present paper a structured mesh was generated using Gmsh and two semi-structured meshes were generated using snappyHexMesh to determine the suitable mesh distribution for simulating unsteady cavitation around a plane convex hydrofoil. The numerical simulation was conducted by using the software OpenFOAM with the k-ω SST SAS turbulence model and the Zwart-Gerber-Belamri (ZGB) cavitation model. Besides, the experimental results obtained by the Laboratory for Hydraulic Machines of École Polytechnique Fédérale de Lausanne were used to validate the numerical results. The results showed that both structured and semi-structured meshes predicted the cavitation pattern and the maximum cavity length. The semi-structured mesh with suitable refinement reproduced in detail the dynamic behavior of unsteady cavitation, while the structured mesh efficiently reproduced the phenomenon.